Usulan Perbaikan Pengendalian Persediaan Spare Part Utama Gondola Menggunakan Metode EOQ dan Min-Max - Santika Sari; Ajeng Puspita Sari; Annisa Putriana Saputro; Nurfajriah Nurfajriah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
PT. Pola Gondola Adiperkasa is a company engaged in construction, whose main activities are gondola maintenance and gondola installation. According to an interview conducted with PT. Pola Gondola Adiperkasa, it is known that this company has problems in unstructured inventory. If the gondola spare part inventory is stored for a long time then the problem that occurs is the reduced quality of the goods. This causes the inventory cost to increase. The purpose of this study is to determine the calculation of the Economic Order Quantity (EOQ) method, to know the calculation of the Min-Max method and to propose improvements regarding inventory control. The results of calculations using the Economic Order Quantity (EOQ) method were found to be more efficient in terms of controlling the gondola spare part inventory compared to PT. Pola Gondola Adiperkasa and Min-Max method. The difference between the policies of PT. Pola Gondola Adiperkasa with Economic Order Quantity (EOQ) method is Rp. 384,787, while the difference between the policies of PT. Pola Gondola Adiperkasa with the Min-Max method is Rp.268.931. Researchers propose to PT. Pola Gondola Adiperkasa to use the Economic Order Quantity method.